IMPACT ONLINE GAMES FOR TEENS IN WELL GORONTALO CITY - YASMIN YUSUF; ABD. HAMID ISA; ABDUL RAHMAT (International Journal of Innovations in Engineering Research and Technology, 2021)
Yasmin Jusuf. Student ID 714 518 001. Impact of Online Game for Adolescent in Villange of Dulalowo Timur, Sub-districk of Kota Tengah, Gorontalo City. 2020. Journal. Department of Non-Formal Education. graduate program. State University of Gorontalo. Principal supervisor Dr. Abdul Rahmat, S.Sos.I.M.Pd This research aims describe impact of online game for adolescent in the Villange of Dulalowo Timur, Sub-district of Kota Tengah, Gorontalo City. This is a qualitative research. Data of the research are collected throught observasion, documentation and interview. Informants are player of online game, parents and owner of the online game determined by purposive sampling. Data of the research are analyzed through data reduction, presentation and conclusion drawing. Data falidity of the research is used persistence of observation, triangulation and relevant references. Research findingreveals that online game has both positive and negative impacts including aspects of physical, social and psychological. Therefore, the adolescents are expected to be wiser in using their time to play online game. Then, the parents are also expected to be able to supervise and control all behaviors of the children.